A study and appreciation of Claude Monet's Artistic creation and life experience / Ge Yao and Zainuddin Abindinhazir - Yao, Ge; Abindinhazir, Zainuddin (Universiti Teknologi MARA, Perak, 2023)
Claude Monet an outstanding Impressionist painter in the 19th century, is one of the founders of Impressionist painting, known as the "father of Impressionism". His representative works include Impression of Sunrise, Cathedral of Rouen, Haystack, and Water Lily. Many artists and scholars in the study of Monet's works, summed up the artist Monet can be famous for the reason: thanks to his unique insight and innovation in painting creation. Every seemingly insignificant change over time will eventually add up and change things qualitatively. This paper makes a correlation analysis between Monet's painting style and his life experience to explore the influence of the painter's life experience on the painting methods adopted at that time, to study and appreciate his representative works which have achieved periodic success. When people not only stop to appreciate the color surface of the work, but also understand the story behind the creation of art, this will more vividly and truly restore the character image of a writer, and further explore the connotation, historical status, and influence on the development history of painting. At the same time, it is beneficial to broaden the richness of the history of art painting and is also of great benefit to the field of art education and academic research. Claude Monet (1840-1926) was a French Impressionist artist known for his innovative methods of painting as well as his iconic landscapes and seascapes. Considered one of the most influential artists of the 19th and early 20th centuries, he is often hailed as a master of capturing the fleeting effect of light and atmosphere in his work.